Pancasila-Based Neutral Center as a Global Conflict Peace Catalyst and Conflict Resolution - Andi Nur Oktafiana; Wilda Rizkiya; Arik Cahyani (Publication of the International Journal and Academic Research, 2025)
In the face of geopolitical instability and ongoing international conflicts, the concept of a "Pancasila-Based Diplomacy Center" is emerging as a relevant alternative strategy for promoting global peace. Pancasila, which embodies values such as humanity, social justice, and unity, offers a moral framework that can address global disparities. Indonesia’s experience in maintaining diversity amidst domestic challenges suggests that Pancasila could serve as a diplomatic model for resolving international conflicts. This study explores the application of Pancasila values in international diplomacy, particularly in dispute resolution. Using a quantitative approach with a quasi-experimental design, the research will examine the relationship between national issues and Pancasila, comparing diplomacy grounded in Pancasila with other diplomatic models, such as those focused on human rights and democracy. The comparison will highlight the effectiveness of the Pancasila-based strategy in fostering inclusive and sustainable peace. Ultimately, the research aims to advance the theory of value-based diplomacy and initiate a new discourse on Indonesia’s role in promoting global peace. It emphasizes the importance of establishing a Pancasila-Based Diplomacy Center within the next five years, positioning Indonesia as a key player in global conflict resolution. By implementing Pancasila as the foundation for international diplomacy, Indonesia can contribute to a more inclusive, equitable, and peaceful global order, despite the challenges of gaining international acceptance for its principles.